Arundhati Roy’s The God of Small Things as the Story of Childhood: Children’s Perspective of Traumatic Experiences - Dhami, Prem Bahadur (SCHOLARS: Journal of Arts & Humanities, 2021)
This paper analyzes the novel The God of Small Things written by Arundhati Roy, which is the childhood reflection of her own. The novel reflects the seduction and solicitation and its psychological impacts on the characters as they are affected by the society, especially by the elite people and the government officials. The novel is analyzed using the concepts of childhood studies – particularly Joseph L. Zornado’s concept of “Black Pedagogy” as the tool for textual analysis. The self-cited statements of the characters provide additional strength to the tool. Roy by the help of various characters like Estha, Velutha, Ammu and Rahel depicts the suffering due to the caste and class differences among the society and the high profile people.